Antimicrobial Resistance of Staphylococcus aureus Strains Acquired by Pig Farmers from Pigs - Oppliger, Anne (American Society for Microbiology, 2012)
Carriage of animal-associated methicillin-resistant Staphylococcus aureus (MRSA) clonal complex 398 (CC398) is common among pig farmers. This study was conducted (i) to investigate whether pig farmers are colonized with pig-specific S. aureus genotypes other than CC398 and (ii) to survey antimicrobial resistance of S. aureus isolates from pigs and pig farmers. Forty-eight S. aureus isolates from pig farmers and veterinarians and 130 isolates from pigs collected in Western Switzerland were genotyped by spa typing and amplified fragment length polymorphism (AFLP). Antimicrobial resistance profiles were determined for representative sample of the isolates. The data obtained earlier on healthy S. aureus carriers without exposure to agriculture were used for comparison. The genotype composition of S. aureus isolates from pig farmers and veterinarians was similar to isolates from pigs with predominant AFLP clusters CC398, CC9, and CC49. The resistance to tetracycline and macrolides (clarithromycin) was common among the isolates from farmers and veterinarians (52 and 21%, respectively) and similar to resistance levels in isolates from pigs (39 and 23%, respectively). This was in contrast to isolates from persons without contact with agriculture, where no (0/128) isolates were resistant to tetracycline and 3% of the isolates were resistant to clarithromycin. MRSA CC398 was isolated from pigs (n = 11) and pig farmers (n = 5). These data imply that zoonotic transmission of multidrug-resistant S. aureus from pigs to farmers is frequent, and well-known MRSA transmission merely represents the tip of the iceberg for this phenomenon. We speculate that the relatively low frequency of MRSA isolation is related to lower antimicrobial use in Switzerland compared to, for example, the Netherlands.